2013
DOI: 10.1523/jneurosci.4068-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Learning Increases Intrinsic Excitability of Hippocampal Interneurons

Abstract: Learning-related intrinsic excitability changes of pyramidal neurons via modulation of the postburst afterhyperpolarization (AHP) have been repeatedly demonstrated in multiple brain regions (especially the hippocampus), after a variety of learning tasks, and in multiple species. While exciting and important, the changes in pyramidal neurons are only a part of the neural circuitry involved in successful learning. For a more complete picture of the dynamic learning-related changes in the neural network, changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 36 publications
6
72
1
Order By: Relevance
“…Importantly, a recent study shows that following classical conditioning of the eye-blink response, hippocampal somatostatin-positive inhibitory interneurons are more excitable, and thus their inhibitory synaptic inputs onto pyramidal neurons are enhanced (McKay et al 2013). Such enhanced GABA release was not observed in our present and previous (Saar et al 2012) studies.…”
Section: Learning-induced Modulation Of Gaba B -Dependent Postsynapticontrasting
confidence: 66%
See 1 more Smart Citation
“…Importantly, a recent study shows that following classical conditioning of the eye-blink response, hippocampal somatostatin-positive inhibitory interneurons are more excitable, and thus their inhibitory synaptic inputs onto pyramidal neurons are enhanced (McKay et al 2013). Such enhanced GABA release was not observed in our present and previous (Saar et al 2012) studies.…”
Section: Learning-induced Modulation Of Gaba B -Dependent Postsynapticontrasting
confidence: 66%
“…For example, activity-induced enhancement in the number of GABA A receptor was shown in the hippocampus after kindling (Nusser et al 1998), and enhanced GABA release was shown after brain-derived neurotrophic factor application (Ohba et al 2005). In a particularly interesting recent study, it was shown that learning of the eye-blink conditioning results in enhanced intrinsic excitability of hippocampal somatostatin-positive inhibitory neurons and that results enhanced inhibition onto CA1 pyramidal neurons (Mckay et al 2013). Our laboratory previously showed that OD learning results in long-lasting enhancement of inhibitory synaptic transmission onto proximal dendrites of piriform cortex layer II pyramidal neurons (Brosh and Barkai 2009).…”
mentioning
confidence: 99%
“…Activation of SK channels blocks conditioning-induced excitability changes in both CA1 pyramidal neurons and interneurons, and impairs learning (McKay et al, 2012, 2013). Because SK channels play a critical role in regulating after hyperpolarizing (AHP) currents and thus firing rates in CA1 (Pedarzani et al, 2005), excitability changes associated with SK channel reductions may mediate the firing rate increases we see in vivo after CFC.…”
Section: Discussionmentioning
confidence: 99%
“…In the hippocampus, the structure that is central to our concepts of memory for places and events (Garner et al, 2012; Mayford, 2014; Takeuchi et al, 2014), and even procedural learning (Micheau et al, 2004), recent studies show evidence of changed hippocampal neural and synaptic function after the acquisition of a hippocampus-dependent memory (Gruart et al, 2006; Whitlock et al, 2006; Matsuo et al, 2008; McKay et al, 2013; Park et al, 2015). While these studies support the synaptic plasticity and memory hypothesis, there still is an absence of direct evidence that persistent hippocampal synaptic function accompanies long-term hippocampus-dependent memory.…”
Section: Introductionmentioning
confidence: 99%